Examining the association between work stress, life stress and obesity among working adult population in Canada: findings from a nationally representative data - Nigatu Regassa Geda; Cindy Xin Feng; Yamei Yu (BMC, 2022)
Abstract Background Obesity is a priority public health concern in Canada and other parts of the world. The study primarily aims at assessing the role of  self-perceived work and life stress on obesity among working adults in Canada. Methods The study was conducted based on a total of 104,636 Canadian adults aged 18 and above, extracted from the 2017-2018 Canadian Community Health Survey (CCHS) data. We used a mixed-effect logistic regression model to determine the possible association between two stress variables and obesity, controlling for other variables in the model. The random effect term accounts for the correlation among the observations from the same health region. Results A total of 63,815 adult respondents (aged 18 and above) who were working during the 12 months prior to the survey were studied. Of those, 18.7% were obese based on their self-reported BMI > =30.0 kg/m2. More than two-thirds of the respondents reported that their stress level is a bit stressful to extremely stressful. The results of multivariable mixed-effect logistic regression showed that the odds of obesity were 1.432 times (95% CI: 1.248-1.644) among those who reported extremely work-related stress, compared to those who had no work-related stress. Perceived life stress was not significantly associated with obesity risk among working adult population, after adjusting other factors. Conclusion The study concluded that obesity among Canadian adults is 18.7% of the working adult population being obese. Given the reported high prevalence of stress and its effect on obesity, the findings suggested improving social support systems, individual/group counseling, and health education focusing on work environments to prevent and manage stressors and drivers to make significant program impacts.